Prototyping a Secure Key Management System: Integrating RFID and Keypad Technologies for Enhanced Safe Protection - Hilda Maulida; Ihsan Riga Valendi; Olland Nugraha; Fadhli Ranuharja (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
This research develops a secure key management system prototype by integrating Radio Frequency Identification (RFID) and keypad technologies to enhance the protection of safes. Safes are widely used for storing valuable assets, but traditional locking systems are vulnerable to unauthorized access. The system combines RFID for user identification and a keypad for password entry, providing a dual-layer security mechanism. The methodology involves a prototyping approach, allowing iterative development and refinement of the system. The system utilizes Arduino Uno as the main controller, with additional hardware components such as an RFID reader, keypad, LCD, and servo motor for door control. Testing of the system demonstrates successful functionality, including identification of valid and invalid RFID tags, password verification, and access control through the servo motor. The results show that the system significantly enhances the security and convenience of accessing the safe, minimizing the risk of unauthorized entry. Future improvements include the development of a user interface for easier password management and full-scale implementation on real safes.